Identification of HOTS-Based Islamic Education Tests in Junior High Schools : an Approach Bloom's Taxonomy and Rasch Model - Pitriani, Pipit; Ma'mur, Ilzamudin; Nugraha, Enung; Wasehudin; Habibi, Muhammad (IAIN PAREPARE, 2024)
Background: Higher-Level Thinking Skills (HOTS) are thinking abilities that need not only the ability to remember, but also the ability to think creatively and critically. Research Objectives: This study identifies and analyzes the level of questions on the Islamic education Examination and analyzes the standardization of question items using the Rasch model technique. Methods: Mixed method for analyzing document data with 160 multiple-choice questions. A quantitative approach was utilized to assess the quality of standard questions based on 31 students' accessible answer data. The document data was examined logically utilizing Bloom's Taxonomy Theory. Meanwhile, the data from students' answers was evaluated using the Item Response Theory (IRT) 1-parameter logistic model, also known as the Rasch model Conclusions: The result shows that many PAI subject questions are still at the LOTS level. Meanwhile, in terms of the quality of the item test using the Rasch model approach, it was found that many items were still not fit, even though in general the reliability of the items was categorized as quite good.